Incidence and Reappraisal of Known Risk Factors Associated with Carpal Tunnel Syndrome: A Nationwide, 11-Year, Population-Based Study in South Korea - Rhee, Seung Yeon; Cho, Han Eol; Kim, Jong Hun; Kim, Hyoung Seop (Journal of clinical neurology (Seoul, Korea), 2021)
Previous studies have revealed various risk factors for carpal tunnel syndrome (CTS), but few large-scale studies have been conducted. We used data from the 11-year, longitudinal, nationwide population-based National Health Insurance Service-National Health Screening cohort to identify the actual risk factors for CTS.BACKGROUND AND PURPOSEPrevious studies have revealed various risk factors for carpal tunnel syndrome (CTS), but few large-scale studies have been conducted. We used data from the 11-year, longitudinal, nationwide population-based National Health Insurance Service-National Health Screening cohort to identify the actual risk factors for CTS.We collected patients with CTS newly diagnosed using electrodiagnostic studies while excluding radiculopathy, plexopathy, or polyneuropathy, which can be confused with CTS. The crude and standardized incidence rates of CTS were calculated. Univariate and multivariate Cox analyses and the incidence of CTS were used to identify the risk factors for newly diagnosed CTS.METHODSWe collected patients with CTS newly diagnosed using electrodiagnostic studies while excluding radiculopathy, plexopathy, or polyneuropathy, which can be confused with CTS. The crude and standardized incidence rates of CTS were calculated. Univariate and multivariate Cox analyses and the incidence of CTS were used to identify the risk factors for newly diagnosed CTS.The standardized incidence was 130.8/100,000 person-years based on the World Health Organization World Standard Population as a reference. Multivariate Cox analysis identified that the risk factors for CTS were being middle-aged, female, and obese, and having rheumatoid arthritis and Raynaud's syndrome, whereas gout and hypothyroidism were not risk factors. Diabetes and end-stage renal disease did not show a significant hazard ratio, although it is implicit that the durations of these diseases affect the development of CTS.RESULTSThe standardized incidence was 130.8/100,000 person-years based on the World Health Organization World Standard Population as a reference. Multivariate Cox analysis identified that the risk factors for CTS were being middle-aged, female, and obese, and having rheumatoid arthritis and Raynaud's syndrome, whereas gout and hypothyroidism were not risk factors. Diabetes and end-stage renal disease did not show a significant hazard ratio, although it is implicit that the durations of these diseases affect the development of CTS.This study calculated the incidence of CTS and reappraised the associated risk factors found in previous studies. This information will be helpful for determining the pathophysiology of CTS, and hence aid the establishment of effective new public health policies.CONCLUSIONSThis study calculated the incidence of CTS and reappraised the associated risk factors found in previous studies. This information will be helpful for determining the pathophysiology of CTS, and hence aid the establishment of effective new public health policies.